RANCANG BANGUN ALAT PEMUPUK JAGUNG TIPE DORONG - Agustiawan, Agustiawan; Jamaluddin, Jamaluddin; Rais, Muhammad (Universitas Negeri Makassar, 2018)
This study aims to determine the working mechanism of push type corn fertilization comparedÂ corn manual fertilization and to find out the comparison of the results of push type corn fertilizers with manual fertilization. The form of this research is get up design, research data obtained from the results of testing tools by conducting a trial comparison between fertilization using push type corn fertilization with manual fertilization, design of push type corn fertilizers designed to produce adjustable fertilizer distance so that it can adjust the distance of the plant and the dose of fertilizer that can be adjusted from 2 to 30 grams. In this test fertilization using corn fertilization with the operation of 1 person and manual fertilization by means of using 2 people, the results of this study were carried out in the corn field. Data analysis techniques were carried out quantitatively with descriptive statistics. The results showed that the push type maize fertilization produced fertilizing grooves with an average of 27.36 meters in 2 minutes, averaging 59.4 meters in 4 minutes, averaging 90.26 meters in 6 minutes, when compared to manual fertilizationÂ produced an average of 27.81 meters in 2 minutes, averaging 56.94 meters in 4 minutes, averaging 80.86 meters in 6 minutes.